Flow induced coalescence in polymer blends - Juza, Josef; Fortelny, Ivan (Lviv Polytechnic Publishing House, 2013)
A modified theory of coalescence induced by extensional flow in polymer blends with Newtonian droplets in viscoelastic matrix has been derived. Results of this theory are compared with results of the theory of shear flow induced coalescence. Elasticity of the matrix leads to a decrease in the coalescence probability. Розроблена модифікована теорія коалесценції індукованої екстенсіональним потоком в полімерних сумішах з ньютонівськими крапельками у в'язкоеластичній матриці. Результати теорії порівняні з результатами теорії зсуву поточної індукованої коалесценції. Встановлено, що еластичність матриці приводить до зменшення ймовірності коалесценції.
Потокова індукована коалесценція в полімерних сумішах
Keywords: coalescence; polymer blends; extensional flow; viscoelasticity; коалесценція; полімерні суміші; екстенсіональний потік; в'язкоеластичність